URGENSI KEWENANGAN MAHKAMAH KONSTITUSI DALAM PENGUJIAN DAN PENGADUAN KONSTITUSIONAL ATAS UNDANG-UNDANG NON-MEANINGFUL PARTICIPATION - Anajeng Esri Edhi Mahanani,; Andina Elok Puri Maharani, (JIL : Journal of Indonesian Law, 2024)
This study aims to analyze the urgency of the authority of the Constitutional Court in Constitutional Testing and Constitutional Complaints on the Non Meaningful Participation Law or in other words the law was formed by violating the democratic rights of the community. Laws must be formed based on the will of the people. The people as the highest holder of sovereignty are the focus of every law formation, so that the law has good validity in society. The formation of laws with non-meaningful participation, or pseudo-degree laws that lack or even negate people's participation is prone to formal testing. The research uses normative juridical method with literature study. The results showed that two mechanisms, namely formal constitutional testing of laws and constitutional complaints, can be used to test laws that are not participatory. However, currently constitutional complaints do not exist in Indonesia, so strengthening formal testing even for each before testing the law materially becomes important. Constitutional complaints can be the last alternative in the future, for decisions that still cannot provide justice and benefit to the holders of sovereignty, namely the people.